Pengaruh Penggunaan Media Audio Visual Terhadap Perilaku Belajar Siswa Pada Mata Pelajajaran PAI - Resa Anzela; Umar Rosadi (Journal of Teacher Training and Educational Research, 2023)
The purpose of this study was to determine whether there is an influence of the use of audio-visual media on student learning behavior in PAI subjects. This study used a quantitative approach descriptive method, data collection techniques using questionnaires and observation. instrument Analysis (data validity and data reliability), Classical Assumption Test, namely: Data Normality Test, Data Linearity Test, Hesterokedasticity Test. And Statistical Analysis i.e. Simple Linear Regression Analysis, Correlation Coefficient Analysis, Descriptive Statistical Analysis and t-Test Hypothesis Testing. The results of this study show that the use of audio-visual media has a significant influence on student learning behavior. The use of audio-visual media obtained calculated t values = 2.230 > 2.035 = t table, and Sig. = 0.03 < 0.05 (5%), so Ho was rejected and H_a accepted. This means that the use of audio-visual media has a significant effect on student learning behavior